Pedagogical Conditions For Improving The Quality Of Professional Education In The Study Of Descriptive Geometry At Higher Education Institutions - Atakhanova S. O. (Euro Asian Journal Publishing, 2024)
The article proposes the ways of formation and professional development of the subjective position of students on the basis of the relationship between the systems of teaching and learning in the practice of teaching a university, which is considered as an integral, interconnected complex with an invariant of relations. The materials are based on the concepts of systems theory, control theory and didactics
Keywords: training system; professional education; descriptive geometry